A biopsy analysis support system for the detection and classification of breast cancer nuclei - Pattichis, Constantinos S.; Schnorrenberg, Frank; Tsapatsoulis, Nicolas; Pattichis, Marios S.; Kyriacou, Kyriacos C. (My University, 2006)
Part-V is dedicated to some of the advanced computer-aided detection techniques applied to architectural distortion
Keywords: Biopsy analysis; Breast cancer nuclei